Spatial control of hairy protein expression during embryogenesis. - Hooper, K.L.; Parkhurst, S.M.; Ish-Horowicz, D. (Development, 1989)
We have used a polyclonal antiserum specific for the Drosophila segmentation gene, hairy (h), to analyse its expression during embryogenesis. The pattern of wild-type expression resembles that of h transcription, being expressed in stripes at the blastoderm stage. h is also expressed later in the stomodaeum, proctodaeum, tracheal pits and mesoderm. We demonstrate that h protein stripes show consistent phase relationships to those of the even-skipped (eve) pair-rule gene. We examine h protein patterns in embryos mutant for other segmentation genes, including h itself. We show that lack of h activity appears not to affect h striping, arguing that h expression is not under autoregulatory control. We also show that h activity is not needed for tracheal invagination. Mutations that are rearranged upstream of the h gene cause the loss of specific stripes, indicating that the h promoter includes activating elements that respond to specific spatial cues. Our observations suggest that pair-rule striping may be under redundant control, and we discuss possible implications for hierarchical models of pair-rule gene action.